Retinal Microcirculation Defects on OCTA Correlate with Active Inflammation and Vision in Vogt–Koyanagi–Harada Disease. (17th November 2021) - Liang, Anyi; Zhao, Chan; Jia, Shanshan; Gao, Fei; Han, Xiaoxu; Pei, Minghang; Qu, Yi; Xiao, Junyan; Zhang, Meifen
ABSTRACT: Purpose : To analyze quantitative OCT-angiography (OCTA) measurements of Vogt-Koyanagi-Harada (VKH) disease at different disease stages. Methods : OCTA scans of 110 VKH patients in acute uveitic, convalescent and chronic recurrent stage were reviewed; posterior uveitis recurrent cases were excluded. Superficial and deep capillary plexus (SCP and DCP) vascular densities (VD) and subfoveal choroidal thickness (SFCT) were compared. Results : DCP VD was significantly lower and SFCT higher in VKH than normal controls (NC) in all 3 stages (all p < .001). Anterior uveitis recurrent patients had lower SCP and DCP VDs and thicker SFCT than convalescent patients ( p = .001, p < .001, and p = .003, respectively). DCP VD was significantly correlated with visual acuity ( p < .05). Patients with history of anterior recurrence had lower retinal VDs in the convalescent stage than those without ( p < .001). Conclusion : Retinal microcirculation is impaired in VKH. DCP VD might be a sensitive indicator of inflammatory status and appeared to be well associated with visual outcome.